Gender Differences in Metacognitive Awareness: A Study on Pre-Service Physics Teachers - Ramadani, Cahyani Intan; Purwaningsih, Endang; Latifah, Eny (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This research aims to analyze gender-based differences in metacognition awareness among pre-service physics teachers. The research sample consisted of 55 first semester active students selected using cluster random sampling. Data were collected using the Metacognitive Awareness Inventory (MAI) questionnaire and analyzed by independent t-test, which showed a significant difference (p = 0.000) between females (78.31) and males (70.26) students. Females score higher in Procedural Knowledge, while males were higher in Debugging Strategies. However, both had the lower score on Information Management Strategies, indicating difficulty in managing information during learning. These findings provide important implications in designing teaching strategies that are more suitable to the differences in metacognitive awareness between males and females, which can have an impact on learning outcomes that can support students' awareness in learning and thinking more effectively.